Development Of Math Blind Game With Voice And QR-Code As Learning Media For Blind Students - Arimbi, Qyara Melia; Irmita, Luthfia Ulva; Wardaya, Anton (Universitas PGRI Semarang, 2024)
Math is a lesson that is difficult for children in Indonesia to understand. Especially in children with visual or blind disorders. This disorder makes it difficult for metematics to study, for in matematics it takes sight to read material to enhance the learning system. This study was developmental research that aimed to describe the result of instructional media development of math blind game with voice and QR code and describe their understanding after using math blind game with voice and QR code as learning media at special needs elementary school. The subject of this study is blind students grade 4th – 6th . The research model used was ADDIE development model (analysis, design, development, implementation, and evaluation). Data were collected using test and questionnaire to know their understanding of math blind game with voice and QR code as lerning media. The result showed that blind students responded positively with an average score of SUS score 83,75 (grade A). Therefore, it can be concluded that math blind game with voice and QR code can be used in teaching and learning activity to improve blind students’ understanding about matematics.